Synthesis, Characterization and Flocculation Performance of Cationic Polyacrylamide P(AM-DMD) - Zhang, Peng; Zhang, Xue; Zhang, Yanjun; Ren, Bozhi; Li, Xuemei; Zhang, Wei (Asian Journal of Chemistry, 2014)
Polymerization of acrylamide and dimethyl diallyl ammonium chloride P(AM-DMD) has been formed by using dimethyldiallylammonium chloride (DMDAAC) and acrylamide (AM) initiated by (NH4)2S2O8 under the condition of microwave. The effect of reaction variables such as microwave time, reactants ratio, dosage of EDTA, dosage of initiator and dosage of sodium benzoate were investigated and the product was detected and characterized by IR spectroscopy and electron microscope scanning. The IR characterization results showed that the synthesized product was a copolymer of acrylamide and dimethyldiallylammonium chloride, The SEM image were depicted that the surface morphology of P(AM-DMD) as an irregular surface with overlapping junctions. The results showed that the optimum conditions were the microwave time was 1.5 min, the reactants ratio(AM:DMD) was 2: 18,the dosage of EDTA was 8 mg, the dosage of initiator was 8 mg, the dosage of sodium benzoate was 4 mg. In addition, P(AM-DMD) had better flocculation efficiency than commercial PAC in turbidity and UV254 removing experiment, using the PAC and P(AM-DMD) had better effect than using single P(AM-DMD) and single PAC.